Cyclodextrins as Multifunctional Platforms in Drug Delivery and Beyond: Structural Features, Functional Applications, and Future Trends - Iuliana Spiridon; Narcis Anghel (Molecules)
Cyclodextrins (CDs) are cyclic oligosaccharides capable of forming inclusion complexes with various guest molecules, enhancing solubility, stability, and bioavailability. This review outlines the structural features of native CDs and their chemically modified derivatives, emphasizing the influence of functionalization on host–guest interactions. Synthetic approaches for CD derivatization are summarized, with attention to recent developments in stimuli-responsive systems and targeted drug delivery. Analytical techniques commonly employed for characterizing CD complexes, such as spectroscopy, thermal analysis, and molecular modeling, are briefly reviewed. Applications in pharmaceutical formulations are discussed, including inclusion complexes, CD-based conjugates, and nanocarriers designed for solubility enhancement, controlled release, and site-specific delivery. Special consideration is given to emerging multifunctional platforms with biomedical relevance. The regulatory status of CDs is addressed, with reference to FDA- and EMA-approved formulations. Safety profiles and toxicological considerations associated with chemically modified CDs, particularly for parenteral use, are highlighted. This review presents an integrative perspective on the design, characterization, and application of CD-based systems, with a focus on translational potential and current challenges in pharmaceutical development.